2022
DOI: 10.1039/d2nj02589b
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring benzo[α]phenoxazine moiety for efficient photosensitizers in dye sensitized solar cells via the DFT/TD-DFT method

Abstract: Three benzo[]phenoxazine-based dyes have been designed by tailoring donor (D) and anchoring (A) moiety to benzo[]phenoxazine template via DFT and TD-DFT method for Dye-sensitized solar cells (DSSCs) application. The transformation...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…The four main components used in the fabrication of DSSCs are the photoanode material (semiconductor), the dye molecule (a photosensitizer), the redox electrolyte, and the counter electrode. In 1991, Grätzel and O’Regan published the first study on DSSCs using N3 dye as a photosensitizer . Numerous studies in this field since the original work on DSSCs have primarily shown that various dyes (photosensitizers) have been molecularly engineered and used in DSSCs. The production of novel photosensitizers that can be developed in DSSCs is an essential component affecting device efficiency. …”
Section: Introductionmentioning
confidence: 99%
“…The four main components used in the fabrication of DSSCs are the photoanode material (semiconductor), the dye molecule (a photosensitizer), the redox electrolyte, and the counter electrode. In 1991, Grätzel and O’Regan published the first study on DSSCs using N3 dye as a photosensitizer . Numerous studies in this field since the original work on DSSCs have primarily shown that various dyes (photosensitizers) have been molecularly engineered and used in DSSCs. The production of novel photosensitizers that can be developed in DSSCs is an essential component affecting device efficiency. …”
Section: Introductionmentioning
confidence: 99%